The relationship between dietary vitamin B1 intake and severe abdominal aortic calcification among the general population in the United States - Li, Hanbo; Li, Ruihua; Gong, Changle; Wu, Zhe; Jia, Qiang (Frontiers in Cardiovascular Medicine, 2024)
BackgroundVitamin B1 deficiency is closely associated with vascular system damage, but the relationship between dietary vitamin B1 intake and abdominal aortic calcification (AAC) remains unclear and warrants further investigation.Methods2,640 participants from the National Health and Nutrition Examination Survey (NHANES) 2013–2014 were included in the study. Severe AAC was defined as Kauppila score >5. Multivariable logistic regression analysis and restricted cubic splines (RCS) were used to examine the relationship between dietary vitamin B1 and severe AAC.ResultsThe increase in dietary intake of vitamin B1 is significantly correlated with a decrease in the risk of severe AAC (OR: 0.601, 95% CI: 0.406, 0.892). Compared to the first quartile of dietary vitamin B1 intake, the fourth quartile had a significantly reduced risk of severe AAC (OR: 0.358, 95% CI: 0.172, 0.744). RCS indicated a decreasing trend in the risk of severe AAC with increasing dietary vitamin B1 intake.ConclusionOur research findings indicate that the increase in dietary intake of vitamin B1 is significantly associated with a decrease in the risk of severe AAC. Thus, increasing dietary vitamin B1 intake appropriately may reduce the risk of severe AAC.